Systemic Delivery of hGhrelin Derivative by Lyophilizate for Dry Powder Inhalation System in Monkeys - Kahori Miyamoto; Yuko Ishibashi; Tomomi Akita; Chikamasa Yamashita (MDPI AG, 2021)
Ghrelin is the peptide that increases the hunger sensation and food intake and is expected to be clinically applied for treatment of diseases such as cachexia and anorexia nervosa. In the clinical application of ghrelin, injections are problematic in that they are invasive and inconvenient. Thus, we aimed to develop a formulation that can eliminate the need for injections and can be applied clinically. We prepared formulations of an hGhrelin derivative, in which the octanoyl group essential for expression of activity is modified to avoid rapid des-acylation, using lyophilizate for a dry powder inhalation (LDPI) system. The formulation of hGhrelin derivative was optimized by the addition of phenylalanine, of which the fine particle fraction of 5 µm or less was 41.7 ± 3.8%. We also performed pharmacokinetic/pharmacodynamic tests in monkeys using the optimum formulation that can be applied clinically. The absolute bioavailability of inhaled hGhrelin derivative with respect to that intravenously injected was 16.9 ± 2.6%. An increase in growth hormone was shown as an effect of the inhaled hGhrelin derivative similar to intravenous injection. The LDPI formulation can deliver the hGhrelin derivative systemically, and it is expected to be applied clinically as a substitute for injections.